MATHEMATICAL MODELING OF HIBRYD POWER SYSTEM BASE ON SPRING-GRAVITY GENERATOR, WIND FARM, SOLAR PANELS, MICRO HYDRO, AND POWER BANK AS A RENEWABLE SOURCE TO AVOID PLN ELECTRICITY THEFT - R. Tiryono; D. Sakethi; A. Sutrisno; R. Mahatir; M. Assyifa (Journal of Innovation Research and Knowledge, 2026)
Abstract: This paper constructs a mathematical model of power plant based on renewable energy sources including generators of spring-gravity, solar panels, wind turbine, micro hydro, power banks as energy storage, generator units and/or state electricity companies as an alternative source and the useful of photocell as efficiency control strategies, motion sensor for momentary lighting and or wi-fi switches in response to fluctuating demand loads. By combining various types of environmentally friendly power plats, it is hoped that they can accommodate fluctuations in load demant and electricity sources produced in such a way that optimal conditions are accieved, and reability with control parametrization enhancing technique as dynamic switching control methode in response to fluctuating demand loads. Furthermore, with the abundance of renewable energy sources in order to avoid PLN electricity theft.